Backstepping Control of Wind and Photovoltaic Hybrid Renewable Energy System - Marouane El Azzaoui; Hassane Mahmoudi; Karima Boudaraia (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper deals with the interconnected grid hybrid renewable energy system (HRES). The wind energy conversion system (WECS), is built around a wind turbine coupled to a doubly fed induction generator (DFIG). The stator of DFIG is directly related to the grid and the rotor is connected to the grid through back-to-back power converters. The proposed algorithm combines the nonlinear Backstepping approach and the eld orientation applied to control the DFIG. In a rst step, this technique is applied to the side converter rotor (RSC), to control the electromagnetic torque and reactive power, and secondly, it is applied to the grid side converter (GSC) to control the power exchanged with the grid and regulate the DC bus voltage. The PV energy system is composed by the PV array and the DC-DC boost converter which controlled by the MPPT method to extract the optimal power. Simulations results present the performances in terms of set point tracking, stability, and robustness with respect to the variation in wind speed and irradiation.